Women's life writing and early modern Ireland - Eckerle, Julie A., 1971-; McAreavey, Naomi (University of Nebraska Press, 2019)
"Women's Life Writing and Early Modern Ireland focuses on women writing in and about seventeenth-century Ireland"-- Provided by publisher
Keywords: English prose literature -- Irish authors -- History and criticism.; English prose literature -- Women authors -- History and criticism.; English prose literature -- Early modern, 1500-1700 -- History and criticism.; English prose literature -- 17th century -- History and criticism.; Women and literature -- Ireland -- History -- 16th century.; Women and literature -- Ireland -- History -- 17th century.; Ireland -- In literature.; Prose anglaise -- 17e siècle -- Histoire et critique.; Femmes et littérature -- Irlande -- Histoire -- 16e siècle.; Femmes et littérature -- Irlande -- Histoire -- 17e siècle.; Irlande -- Dans la littérature.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; LITERARY COLLECTIONS -- European -- English, Irish, Scottish, Welsh.; English prose literature; English prose literature -- Early modern; English prose literature -- Irish authors; English prose literature -- Women authors; Literature; Women and literature; Ireland; 1500-1700; Criticism, interpretation, etc.; History